IMPLEMENTASI PROGRAM TPBIS PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PADANG PANJANG MELALUI PELATIHAN MENJAHIT BED COVER UNTUK TUNA RUNGU - Syukri, Fitria Diane Pratiwi; Hidayatullah, Fauzan (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2025)
This study aims to determine the Implementation of the Social Inclusion-Based Library Transformation Program and the challenges and obstacles faced by the Padang Panjang City Library and Archives Service. To achieve the objectives of the study, the researcher used a qualitative descriptive approach, where data was obtained from observation, in-depth interviews, and documentation. The results of the study indicate that the Implementation of the Social Inclusion-Based Library Transformation Program at the Padang Panjang City Library and Archives Service has made the surrounding community not only use the Library as a place to read books, borrow and return books, but there they can participate in programs and activities carried out by the Padang Panjang City Library and Archives Service. The activities held can be for all groups, from children, teenagers, housewives and groups of people with disabilities. One form of implementation of the TPBIS program is holding training to make bed covers for the deaf who are members of the Indonesian Disability Association (PDDI). This activity can improve the economy and empower people with disabilities after participating in training held by the Padang Panjang City Library and Archives Service.